2020
DOI: 10.1021/acs.analchem.9b05523
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Lipid Transfer Protein Activity Using Bicelle-Dilution Model Membranes

Abstract: In vitro assessment of lipid intermembrane transfer activity by cellular proteins typically involves measurement of either radiolabeled or fluorescently labeled lipid trafficking between vesicle model membranes. Use of bilayer vesicles in lipid transfer assays usually comes with inherent challenges because of complexities associated with the preparation of vesicles and their rather short “shelf life”. Such issues necessitate the laborious task of fresh vesicle preparation to achieve lipid transfer assays of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Reactions of BODIPY with some membranes as well as intracellular and plasma lipids have been reported as biomarkers of use in diabetes[ 28 - 31 ]. Furthermore, a mix of BODIPYs could be used to determine more than one metabolite linked to diabetes evolution.…”
Section: Bcc As Markers or Labeling Molecules Related To The Origin A...mentioning
confidence: 99%
“…Reactions of BODIPY with some membranes as well as intracellular and plasma lipids have been reported as biomarkers of use in diabetes[ 28 - 31 ]. Furthermore, a mix of BODIPYs could be used to determine more than one metabolite linked to diabetes evolution.…”
Section: Bcc As Markers or Labeling Molecules Related To The Origin A...mentioning
confidence: 99%
“…At the time of original publication, the model membranes used as energy acceptors in the FRET experiments were described as dansyl-PE/POPC/DHPC (5:45:50) bicelles. Based on more recent experiments performed for a 2020 Analytical Chemistry publication ( Gao et al, 2020 ) and further elaborated in a recent (2021) Bio-protocol article ( Gao et al, 2021 ), we now know that describing the energy acceptor model membranes as dansyl-PE/POPC/DHPC bicelles is incorrect. In the Analytical Chemistry paper, we showed that dilution of POPC-DHPC (50:50) ‘bicelle’ lipid mixes to the low micromolar range, as similarly employed and described in the Methods for the FRET experiments involving the C2-domain and mutants, results in nearly immediate transformation into small POPC unilamellar bilayer vesicles containing little or no DHPC.…”
mentioning
confidence: 99%
“…Bicelle -dilution vesicle s were formed by mixing the POPC, dansyl-PE and DHPC in chloroform, drying under a stream of nitrogen and placing under vacuum for ~2 h, before resuspending in buffer (20 mM Tris, pH 7.5, 150 mM NaCl and 50 µM CaCl 2 ). Unilamellar POPC vesicle preparation by POPC/DHPC bicelle mix dilution is detailed in Gao et al, 2020 . Binding reactions included C2–domain (0.5 µM) and various amounts of bicelle -dilution vesicle s (PC conc.…”
mentioning
confidence: 99%
See 1 more Smart Citation